Factors contributing to emergency department care within 30 days of hospital discharge and potential ways to prevent it: Differences in perspectives of patients, caregivers, and emergency physicians. Issue 5 (5th February 2014) - Suffoletto, Brian; Hu, Jennifer; Guyette, Maria; Callaway, Clifton
<x xml:space="preserve">Abstract</x> BACKGROUND Identifying needs in patients who utilize the emergency department (ED) soon after being discharged from inpatient care is essential for planning appropriate care‐transition interventions. OBJECTIVE To examine differences in stakeholder perspectives on reasons for ED care soon after hospital discharge and interventions that could be useful to prevent these ED visits. DESIGN AND MEASUREMENTS A convenience sample of 135 patients who presented to an urban teaching hospital ED <30 days after last hospital discharge, their caregivers (when present), and emergency physicians were administered identical structured surveys. Concordance and agreement rates between patient‐physician and patient‐caregiver dyads were calculated. RESULTS Concordances between stakeholders were poor, with weighted kappas ranging from 0.02 to 0.34 for patient‐physician dyads and 0.03 to 0.68 for patient‐caregiver dyads. Emergency physicians and caregivers identified factors between 1% and 42% of the time the patients did not. Less than half of any stakeholder could identify an intervention to potentially prevent the ED visit. CONCLUSIONS Our findings suggest the difficulty in forming unified definitions for root cause of ED visits soon after hospital discharge and support the use of multiple stakeholders in identifying appropriate targets for care‐transition interventions. Journal of Hospital Medicine 2014;9:315–319. © 2014 Society of Hospital Medicine